Limited Plasmodium sporozoite gliding motility in the absence of TRAP family adhesins - Beyer, Konrad; Kracht, Simon; Kehrer, Jessica; Singer, Mirko; Klug, Dennis; Frischknecht, Friedrich (Malaria journal, 2021)
Plasmodium sporozoites are the highly motile forms of malaria-causing parasites that are transmitted by the mosquito to the vertebrate host. Sporozoites need to enter and cross several cellular and tissue barriers for which they employ a set of surface proteins. Three of these proteins are members of the thrombospondin related anonymous protein (TRAP) family. Here, potential additive, synergistic or antagonistic roles of these adhesion proteins were investigated.
Gesehen am 13.12.2021